Anteseden Sikap Konsumen terhadap Perilaku Pembelian Online - Suhendra, Andy Reyhan; Masnita, Yolanda; Kurniawati (Fakultas Ekonomi Universitas Samudra, 2023)
The purpose of this research is to explore the things that influence consumer attitudes in shopping online, as well as the influence of these attitudes on their behavior in making online purchases. This research was conducted through the perspective of the technology acceptance model (TAM), which is based on consumer value theory. This study uses SEM (structural equation modeling) analysis on primary data based on the results of a questionnaire that has been distributed to 289 respondents. The results show that there is a significant effect of perceived ease of use on attitude, and attitude has a significant effect on online buying behavior. However, perceived usefulness, perceived enjoyment, information availability, and perceived price separately proved to have no effect on attitude. The managerial implications of the findings identify the companies that issue e-commerce must be able to guarantee the convenience available in these applications, so that customer attitudes towards applications will be more positive.